2012
DOI: 10.1074/jbc.m111.306399
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin D Primes Caspase-8 Activation by Multiple Intra-chain Proteolysis

Abstract: Background:The exact mechanism of caspase-8 activation by cathepsin D remains unclear. Results: The generation of an active caspase-8 requires both cathepsin D-mediated proteolysis and homodimerization of caspase-8. Conclusion: Cathepsin D is able to directly activate caspase-8. Significance: Cathepsin D-induced caspase-8 activation may represent a general mechanism to induce apoptosis in the absence of death receptor activation in a variety of immune and nonimmune cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 46 publications
3
25
0
1
Order By: Relevance
“…In melanocytes, UVA-induced apoptosis is mediated by lysosomal membrane permeabilization and release of cathepsins to the cytosol (Bivik et al, 2007). It has been suggested that cathepsin D activates caspase-8 in in vitro experiments (Conus et al, 2008;Conus et al, 2012), which further supports our findings. Cathepsin inhibitors would not only prevent the proteolytic activity of the proteases in the lysosomes but also when cathepsins have been released to the cytosol following lysosomal membrane permeabilization.…”
Section: Discussionsupporting
confidence: 79%
“…In melanocytes, UVA-induced apoptosis is mediated by lysosomal membrane permeabilization and release of cathepsins to the cytosol (Bivik et al, 2007). It has been suggested that cathepsin D activates caspase-8 in in vitro experiments (Conus et al, 2008;Conus et al, 2012), which further supports our findings. Cathepsin inhibitors would not only prevent the proteolytic activity of the proteases in the lysosomes but also when cathepsins have been released to the cytosol following lysosomal membrane permeabilization.…”
Section: Discussionsupporting
confidence: 79%
“…Furthermore, our hypothesis is able to explain previous observations regarding CD cleavage. For instance, the recently reported CD-cleaved sites identified in caspase-8 [13], Bid [39] and Aven [40] contain hydrophobic residues at either P1 or P1’ and are associated with an HSN of more than 1.0. We also carefully examined the sites of CD cleavage reported by Impens et al [33].…”
Section: Discussionmentioning
confidence: 99%
“…Because of dual locations of CD, being either located in organelles such as in the cytoplasm, lysosomes and phagosomes, or secreted into the ECM, it participates in a number of physiological processes, including cell proliferation [12], apoptosis [13], [14], senescence [15] and tissue homeostasis [16]. CD is also known to take part in various pathological processes; it is likely involved in cancer development as well as metastasis [12], [17], atherosclerosis [18], [19] and Alzheimer’s disease [20], [21].…”
Section: Introductionmentioning
confidence: 99%
“…19, 20 Removal of the 44 amino acid N-terminal propeptide produces the 48kD intermediate form and a further proteolytic cleavage results in the CTSD mature form (CTSD-m) consisting of a 34kD and a 14kD chain. 20 With the creation of Ctsd global knockout mice, 21 CTSD has been studied for its role in immune homeostasis 22 , apoptosis, 23 cancer development, 24, 25 neurodegeneration, 26, 27 and retina diseases. 28 Changes in myocardial CTSD expression are also frequently used as an indicator of autophagic activity, assuming a key role for CTSD in lysosomal degradation of autophagosomes; 2931 however, this assumption has not been formally tested.…”
mentioning
confidence: 99%